Electro Clinical Profiles of Motor Neuron Disease and Atypical Motor Neuron Disorders: A Case Series - Debnath, Bithi; Quaderi, Humaira Rafiqa; Haque, Nazmul; Khan, AFM Al Masum; Sabeka, Meera Momtaz; Mian, Md Ferdous; Islam, Md Nahidul; Hussain, Md Enayet; Chowdhury, Rajib Nayan (Journal of National Institute of Neurosciences Bangladesh, 2018)
Amyotrophic lateral sclerosis (ALS) is the commonest MND phenotype. Although many of the atypical motor neuron disorders share some features with ALS, they often can be distinguished by their clinical and electrophysiologic characteristics. Here we present five different cases with varied clinical findings. All the patients were referred from outpatient department to neurophysiology laboratory where electrodiagnostic (EDX) correlations helped to come to a conclusion. The nerve conduction study protocol for a suspected atypi¬cal motor neuron disorder is the same as that for ALS. Akin to the nerve conduction studies, the EMG evaluation of patients with suspected atypical motor neuron disorders is similar to that of ALS. An extensive study is indicated, often of all four limbs, the paraspinal muscles, and the bulbar muscles to reach a possible diagnosis. History, clinical findings and electrophysiological correlation often help to differentiate these atypical motor neuron disorders. Correct diagnosis is needed for further evaluation and prognosis. In this case series five (5) cases have described who are referred from outpatient department to neurophysiology laboratory for electrodiagnostic (EDX) correlations. Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 57-61